Sintering behaviour and properties of magnesium orthosilicate-hydroxyapatite ceramic. Issue 14 (1st November 2016) - Ramesh, S.; Jeffrey, C.K.L.; Tan, C.Y.; Wong, Y.H.; Ganesan, P.; Ramesh, S.; Kutty, M.G.; Chandran, Hari; Devaraj, P.
Abstract: The effect of pressureless sintering on the properties of magnesium orthosilicate-hydroxyapatite (MO-HA) ceramic has been studied. The amount of MO composition in the green body was varied from 10 wt% to 50 wt% through mechanical ball milling and was subsequently sintered at varying temperatures in air atmosphere from 1000 °C to 1300 °C for 2 h. The magnesium orthosilicate phase was stable during sintering but the hydroxyapatite phase decomposed to tricalcium phosphate. The MO-HA composites generally exhibited lower mechanical properties across all the investigated composition. Nevertheless, a high fracture toughness of 2.5 MPam 1/2 was recorded for sintered body that contained 20 wt% MO. This finding indicates the potential of this ceramic composite to be used for biomedical applications.